Sự phản ánh các giá trị gia đình của Mỹ trong seri phim “gia đình hiện đại” - Đào, Quỳnh Trang (2020)
This paper studies on American family values reflected in the movie series ―Modern Family‖. The purpose of this research is to highlight on the outstanding American family values in three different aspects of family patterns, behaviors of members and child rearing; and to reveal how the movie series ―Modern Family‖ express those family values. Hereby, the researcher aims at enriching readers’ understanding of American family life particularly and American cultural values generally. Furthermore, this study is expected to serve as a helpful reference for cross-cultural communication teaching and learning. For the accomplishment of the above purposes, 24 episodes in season 1 of the movie series ―Modern Family‖ are chosen as the subject of the study. In the part of data collection, the researcher uses the method of observation to identify American family values expressed in the characters’ deeds and languages. Then, the approach of qualitative content analysis is adopted for deep data analysis. The result of this study indicates that there are seven major American family values reflected in three different families in the movie series ―Modern Family‖. They are individualism; self-reliance; privacy; competition; equality, informality, openness, directness and